212k views
3 votes
Write a justification for each step. 7x-3=(2x+6) + (3x-3)

User Igor Rivin
by
6.3k points

2 Answers

5 votes

Final answer:

To solve the equation 7x-3 = (2x+6) + (3x-3), we need to simplify the algebraic expression step by step and find the value of x.

Step-by-step explanation:

To solve the equation 7x-3 = (2x+6) + (3x-3), we need to simplify the algebraic expression step by step.

  1. Distribute the addition in the right-hand side. 7x-3 = 2x + 6 + 3x - 3.
  2. Combine like terms. 7x-3 = 5x + 3.
  3. Subtract 5x from both sides to isolate the variable. 2x-3 = 3.
  4. Add 3 to both sides to solve for x. 2x = 6.
  5. Divide both sides by 2 to find the value of x. x = 3.

Now we can check the answer by substituting x=3 back into the original equation. 7(3)-3 = (2(3)+6) + (3(3)-3). Simplifying both sides, we get 18 = 18, which confirms that the solution x=3 is correct.

User Ervin Ter
by
5.9k points
1 vote
This is the answer see it carefully
User Mrunal Thanki
by
6.3k points